Negative pole piece, secondary battery and device

By using acrylic-acrylonitrile copolymer as the negative electrode binder in lithium-ion batteries, controlling the specific surface area of ​​its components and graphite, the insufficient performance of the negative electrode sheet of lithium-ion batteries in terms of fast charging and long life is solved, and the performance of the negative electrode sheet of lithium-ion batteries is achieved. Higher dynamic performance and stability extend the battery life.

CN119252858APending Publication Date: 2025-01-03NIO TECH ANHUI CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411361395.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The negative electrode sheets of existing lithium-ion batteries have insufficient performance in terms of fast charging and long life, especially the volume expansion caused by silicon-based materials during the deintercalation of lithium, resulting in structural instability, affecting the overall performance of the battery.

Method used

The acrylic acid-acrylonitrile copolymer is used as the negative electrode binder. By controlling the content of alkali metal elements, the content of acrylonitrile units and the specific surface area of ​​graphite, the lithium ion migration rate and the stability of the binder are enhanced, and the binder and The adhesion of graphite particles relieves the stress caused by expansion of silicon-based materials.

Benefits of technology

It improves the dynamic performance and stability of lithium-ion batteries, extends the battery's calendar life, and improves the first Coulomb efficiency and calendar life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252858A_ABST
    Figure CN119252858A_ABST
Patent Text Reader

Abstract

The invention relates to a negative pole piece, a secondary battery and a device. The negative pole piece comprises a negative active material layer, the negative active material layer comprises graphite and an acrylic acid-acrylonitrile copolymer binder, and the acrylic acid-acrylonitrile copolymer binder comprises a first acrylic acid unit, a second acrylic acid unit and an acrylonitrile unit, at least one of the first acrylic acid unit and the second acrylic acid unit contains an alkali metal element, and the alkali metal element comprises at least one of Li, Na and K; the negative pole piece meets the condition that (1-Z) * B + W is greater than or equal to 0.2 and less than or equal to 3; wherein based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the alkali metal element is W, and the mass percentage content of the acrylonitrile unit is Z; the specific surface area of the graphite is B, and the unit is m < 2 > / g. Therefore, the negative pole piece and the secondary battery have at least one of the following advantages: excellent first coulombic efficiency and calendar life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and in particular to a negative electrode sheet, a secondary battery and a device. Background Art

[0002] As lithium-ion batteries develop into large-scale application fields such as electric vehicles and renewable energy storage systems, higher requirements are placed on the performance indicators of lithium-ion batteries, such as energy density, power density, and long life. As a new type of energy, the rapid iterative development of power batteries can reduce human dependence on fossil fuels and provide reliable clean energy for green and environmentally friendly travel. The performance of lithium-ion batteries depends largely on the quality and stability of their internal battery components. Among them, the binder, as one of the key materials of the battery component, plays an important role in fixing and connecting the battery components and improving the battery performance. Therefore, improving the bonding performance is conducive to improving the overall performance of the entire battery. At present, the binders widely used in battery negative electrode sheets are mainly styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA). However, the negative electrode binder can still be further optimized in terms of application to improve the performance of the battery.

[0003] Therefore, current negative electrode plates, secondary batteries and devices still need to be improved. Summary of the invention

[0004] At present, power batteries have increasingly higher requirements for fast charging and long life, so there are higher requirements for the kinetics and stability of materials, especially for batteries with silicon-containing negative electrodes. The volume expansion of silicon during the process of lithium insertion and extraction will cause more irreversible structural changes, thereby causing a decrease in battery stability. In addition, due to the different particle sizes and specific surface areas of graphite and silicon-based materials, the contact effect between negative electrode particles and between negative electrode particles and binders will also affect the stability of the battery. Therefore, developing high-kinetic and high-adhesion negative electrode binders is an effective way to improve the contact resistance between particles and the bonding strength between particles and between particles and current collectors. In view of this, the present application provides a negative electrode plate, a secondary battery and a device, which use acrylic acid-acrylonitrile copolymer as a negative electrode binder, and by controlling the content of alkali metal elements, the content of acrylonitrile units, and the specific surface area of ​​graphite in the acrylic acid-acrylonitrile copolymer binder, on the one hand, the lithium ion migration rate is effectively improved, the kinetic performance is increased, the DCR is reduced, and the first efficiency is improved; on the other hand, through the above-mentioned control, the stability of the binder and the hardness of the plate are improved, the adhesion of the binder to the current collector and the adhesion of the binder to the negative electrode graphite particles are simultaneously improved, the toughness of the binder is enhanced, and the stress caused by the expansion of the negative electrode silicon-based material is alleviated, thereby extending the calendar life of the secondary battery using the negative electrode plate as a whole.

[0005] On one hand, the present application provides a negative electrode plate, which includes a negative electrode active material layer, wherein the negative electrode active material layer includes graphite and an acrylic acid-acrylonitrile copolymer binder, wherein the acrylic acid-acrylonitrile copolymer binder includes: a first acrylic acid unit, a second acrylic acid unit and an acrylonitrile unit, wherein at least one of the first acrylic acid unit and the second acrylic acid unit contains an alkali metal element, wherein the alkali metal element includes at least one of Li, Na and K; the negative electrode plate satisfies: 0.2≤(1-Z)×B+W≤3; wherein, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the alkali metal element is W, and the mass percentage content of the acrylonitrile unit is Z; the specific surface area of ​​the graphite is B, and the unit is m 2 / g.

[0006] Another aspect of the present application provides a secondary battery, which includes the negative electrode sheet described above.

[0007] Another aspect of the present application provides a device, which includes the secondary battery described above.

[0008] The beneficial effects of this application are:

[0009] The negative electrode plate provided by the present application uses acrylic acid-acrylonitrile copolymer as the negative electrode binder. By controlling the content of alkali metal elements, the content of acrylonitrile units, and the specific surface area of ​​graphite in the acrylic acid-acrylonitrile copolymer binder, on the one hand, the lithium ion migration rate is effectively improved, the kinetic performance is increased, the DCR is reduced, and the first effect is improved; on the other hand, through the above control, the stability of the binder and the hardness of the plate are improved, the adhesion between the binder and the current collector, and the adhesion between the binder and the negative electrode graphite particles are improved simultaneously, the toughness of the binder is enhanced, and the stress caused by the expansion of the negative electrode silicon-based material is relieved, and the stability of the negative electrode plate in the battery life cycle is enhanced, thereby extending the calendar life of the secondary battery using the negative electrode plate as a whole. Therefore, based on the above improvements, the negative electrode plate and the secondary battery of the present application have at least one of the following advantages: excellent first coulomb efficiency and calendar life. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 The negative electrode plate contains a conventional acrylic acid-acrylonitrile copolymer binder in the prior art.

[0011] Figure 2 An acrylic acid-acrylonitrile copolymer binder according to one embodiment of the present application.

[0012] Figure 3 A negative electrode sheet containing an acrylic acid-acrylonitrile copolymer binder according to one embodiment of the present application.

[0013] Reference numerals:

[0014] 100: graphite; 200: acrylic acid-acrylonitrile copolymer in the prior art; 10: acrylic acid structure; 20: acrylonitrile structure; 300: acrylic acid-acrylonitrile copolymer in the present application; 30: first acrylic acid unit; 40: second acrylic acid unit; 50: acrylonitrile unit. DETAILED DESCRIPTION

[0015] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.

[0016] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0017] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0018] The term "C1-C6 alkyl" includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, and the like.

[0019] The term "C3-C6 cycloalkyl" includes, but is not limited to, cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl and the like.

[0020] The term "C2-C6 alkenyl" includes, but is not limited to, ethenyl, propenyl, butenyl, pentenyl or hexenyl and the like.

[0021] The term "C2-C6 alkynyl" includes, but is not limited to, ethynyl, propynyl, butynyl, pentynyl or hexynyl and the like.

[0022] The term "C6-C12 aryl" includes, but is not limited to, phenyl or naphthyl and the like.

[0023] The term "C6-C12 heteroaryl" refers to an aromatic group having 1-3 heteroatoms as ring atoms, the remaining ring atoms being carbon, and the heteroatoms including oxygen, sulfur or nitrogen, including but not limited to: furanyl, thienyl, pyridyl, pyrrolyl, pyrimidinyl, pyrazinyl or imidazolyl, etc.

[0024] The term "substituted or unsubstituted" means that the functional group recorded after the term may or may not have a substituent. For example, "substituted or unsubstituted C1-C6 alkyl" refers to a C1-C6 alkyl with a substituent or an unsubstituted C1-C6 alkyl. The number of substituents may be 1 or more than 2, and the substituents include at least one of halogen, alkyl, aryl, heteroaryl or cyano. It should be understood that when the number of substituents is greater than 1, each substituent may be the same or different.

[0025] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0026] 1. Negative electrode

[0027] The present application provides a negative electrode plate, which includes a negative electrode active material layer, wherein the negative electrode active material layer includes graphite and an acrylic acid-acrylonitrile copolymer binder, wherein the acrylic acid-acrylonitrile copolymer binder includes: a first acrylic acid unit, a second acrylic acid unit and an acrylonitrile unit, wherein at least one of the first acrylic acid unit and the second acrylic acid unit contains an alkali metal element, wherein the alkali metal element includes at least one of Li, Na and K; wherein the negative electrode plate satisfies: 0.2≤(1-Z)×B+W≤3; wherein, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the alkali metal element is W, and the mass percentage content of the acrylonitrile unit is Z; and the specific surface area of ​​the graphite is B, and the unit is m 2 / g.

[0028] Therefore, reference Figures 1 to 3 Compared with the acrylic acid-acrylonitrile copolymer in the prior art (reference Figure 1 The acrylic acid-acrylonitrile copolymer 200 is composed of an acrylic acid structure 10 and an acrylonitrile structure 20, and is used to form a negative electrode active material layer with graphite 100). The negative electrode plate provided by the present application utilizes the acrylic acid-acrylonitrile copolymer (reference Figures 2-3, the acrylic acid-acrylonitrile copolymer 300 includes a first acrylic acid unit 30, a second acrylic acid unit 40 and an acrylonitrile unit 50, which is used to form a negative electrode active material layer with graphite 100) as a negative electrode binder. By controlling the content of alkali metal elements, the content of acrylonitrile units, and the specific surface area of ​​graphite in the acrylic acid-acrylonitrile copolymer binder, on the one hand, the lithium ion migration rate is effectively improved, the kinetic performance is increased, the DCR is reduced, and the first effect is improved; on the other hand, through the above control, the stability of the binder and the pole piece hardness are improved, the adhesion of the binder to the current collector and the adhesion of the binder to the negative electrode graphite particles are improved simultaneously, the toughness of the binder is enhanced, and the stress caused by the expansion of the negative electrode silicon-based material is relieved, and the stability of the negative electrode pole piece in the battery life cycle is enhanced, thereby extending the calendar life of the secondary battery using the negative electrode pole piece as a whole. Therefore, based on the above improvements, the negative electrode pole piece and the secondary battery of the present application have at least one of the following advantages: excellent first coulomb efficiency and calendar life.

[0029] In some embodiments, the chemical structural formula of the acrylic acid-acrylonitrile copolymer binder is as shown in Formula I:

[0030]

[0031] Wherein, a is an integer greater than 0, b is an integer greater than or equal to 0, and c is an integer greater than 0;

[0032] R1 includes at least one of H, Li, Na and K, and at least one R1 is at least one of Li, Na and K; R2 includes at least one of substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C3-C6 cycloalkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C6-C12 aryl and substituted or unsubstituted C6-C12 heteroaryl, wherein the substituent includes at least one of halogen, alkyl, aryl or heteroaryl.

[0033] The acrylic acid-acrylonitrile copolymer binder has its carboxyl functional group hydrogen position replaced by an alkali metal ion, such as Li +, thus, a lithiated acrylic acid-acrylonitrile copolymer binder is obtained. Compared with the acrylic acid-acrylonitrile copolymer in the prior art (composed of an acrylic acid structure and an acrylonitrile structure, and the acrylic acid unit is not replaced by an alkali metal), the introduction of alkali metal ions improves the lithium ion migration rate, increases the dynamic performance, and reduces the DCR. The lithium ions in the lithiated binder can also be used as active lithium ions in the system, thereby improving the first effect. The molecular weight of the modified acrylic acid-acrylonitrile copolymer is improved compared to the binder in the prior art, thereby improving its stability (Tg), increasing the hardness of the pole piece (compression modulus), and improving the long life. In addition, in the modified acrylic acid-acrylonitrile copolymer, the lithiated part can improve the adhesion with the current collector, and can delay the time for the material to fall off the foil during the continuous lithium deintercalation process, thereby improving the long life. The acrylonitrile unit part can improve the adhesion of the active main material particles, and can improve the toughness of the binder, so that the stress caused by the expansion of the particles can be released in time during the repeated lithium deintercalation of the active main material, delaying the failure cycle of the binder, thereby improving the calendar life.

[0034] In some embodiments, b is an integer greater than 0. In some embodiments, R1 includes at least one of H and Li, and at least one R1 is Li; R2 includes at least one of C1-C3 alkyl, C3-C6 cycloalkyl, C2-C3 alkenyl, C2-C3 alkynyl, C6-C12 aryl and C6-C12 heteroaryl. In some embodiments, R1 includes at least one of H and Li, and at least one R1 is Li; R2 includes C1-C3 alkyl. In some embodiments, the numerical values ​​of a, b, and c are not particularly limited, as long as the respective values ​​can make each structural unit meet the requirements of the mass percentage content (for example, the mass percentage content of the acrylonitrile unit in the acrylic acid-acrylonitrile copolymer binder is 10% to 40%), and the average molecular weight of the acrylic acid-acrylonitrile copolymer binder is 700,000 to 900,000.

[0035] In some embodiments, in the acrylic acid-acrylonitrile copolymer binder, the structural formula of the first acrylic acid unit is The structural formula of the second acrylic acid unit is The structural formula of acrylonitrile unit is Wherein, * represents the connection site, in the acrylic acid-acrylonitrile copolymer binder, the first acrylic acid unit, the second acrylic acid unit and the acrylonitrile unit can appear repeatedly, and R1 and R2 can be the R1 and R2 described above, which will not be repeated here. Compared with the acrylic acid-acrylonitrile copolymer (composed of an acrylic acid structure and an acrylonitrile structure) in the prior art, when the acrylic acid-acrylonitrile copolymer binder is used as a binder in a negative electrode sheet, the first acrylic acid unit can improve the adhesion of the copolymer to the current collector and to the polar particles, and can reduce the energy required for conversion during lithium ion transmission; the second acrylic acid unit can improve the adhesion of the copolymer to graphite particles and increase the toughness of the copolymer; the acrylonitrile unit can improve the adhesion of the copolymer to graphite particles.

[0036] In some embodiments, the average molecular weight of the acrylic acid-acrylonitrile copolymer binder is 700,000 to 900,000. In some embodiments, the average molecular weight of the acrylic acid-acrylonitrile copolymer binder is 700,000, 720,000, 750,000, 780,000, 800,000, 820,000, 850,000, 880,000, 900,000 or any value therebetween.

[0037] In some embodiments, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the first acrylic acid unit is 60% to 90%, and the mass percentage content of the second acrylic acid unit is 0 to 30%. In some embodiments, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the sum of the mass percentage content of the first acrylic acid unit and the second acrylic acid unit is 60% to 90%. In some embodiments, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the first acrylic acid unit is 60%, 70%, 80%, 90% or any value therebetween, and the mass percentage content of the second acrylic acid unit is 0%, 5%, 10%, 15%, 20%, 25%, 30% or any value therebetween. In some embodiments, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the sum of the mass percentage content of the first acrylic acid unit and the second acrylic acid unit is 60%, 70%, 80%, 90% or any value therebetween.

[0038] In some embodiments, the acrylic acid-acrylonitrile copolymer binder includes a copolymer formed by copolymerization of a first acrylic acid monomer, a second acrylic acid monomer and an acrylonitrile monomer and partial substitution with an alkali metal; wherein the chemical structural formula of the first acrylic acid monomer is as shown in Formula II, the chemical structural formula of the second acrylic acid monomer is as shown in Formula II, and the chemical structural formula of the acrylonitrile monomer is as shown in Formula IV:

[0039]

[0040] Wherein, R2 includes substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C3-C6 cycloalkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C6-C12 heteroaryl, wherein the substituent includes at least one of halogen, alkyl, aryl or heteroaryl. In some embodiments, R1 includes at least one of H and Li, and at least one R1 is Li; R2 includes at least one of C1-C3 alkyl, C3-C6 cycloalkyl, C2-C3 alkenyl, C2-C3 alkynyl, C6-C12 aryl and C6-C12 heteroaryl. In some embodiments, R1 includes at least one of H and Li, and at least one R1 is Li; R2 includes C1-C3 alkyl. It should be noted that the first acrylic acid monomer, the second acrylic acid monomer and the acrylonitrile monomer can be copolymerized in an aqueous solution to form an acrylic acid-acrylonitrile copolymer precursor, that is, formed by solution or emulsion polymerization, and then partially substituted by an alkali metal to form a final acrylic acid-acrylonitrile copolymer, wherein the alkali metal partial substitution can be achieved by adding an alkali metal hydroxide solution (such as an aqueous LiOH solution) to the acrylic acid-acrylonitrile copolymer precursor to replace the position of H in -COOH, and the final acrylic acid-acrylonitrile copolymer binder (PAA-Li-PAN) solution to be obtained can also be determined by adjusting the amount of LiOH added and monitoring the pH value, for example, the mass percentage of the Li element can be controlled to be 2.8%.

[0041] In some embodiments, when the first acrylic acid monomer, the second acrylic acid monomer and the acrylonitrile monomer are copolymerized, the molar ratio of the first acrylic acid monomer, the second acrylic acid monomer and the acrylonitrile monomer is 1:(0.5-1.5):(0.5-1.5). In some embodiments, the molar ratio of the first acrylic acid monomer, the second acrylic acid monomer and the acrylonitrile monomer is 1:0.5:0.5, 1:0.5:1, 1:0.5:1.5, 1:1:0.5, 1:1:1, 1:1:1.5, 1:1.5:0.5, 1:1.5:1, 1:1.5:1.5 or any value therebetween. In some embodiments, the molar ratio of the first acrylic acid monomer, the second acrylic acid monomer and the acrylonitrile monomer is 1:1:1.

[0042] In some embodiments, 0.2≤(1-Z)×B+W≤3. In some embodiments, (1-Z)×B+W is 0.2, 0.5, 0.8, 1, 1.5, 2, 2.5, 3 or any value therebetween. In some embodiments, 0.2≤(1-Z)×B+W≤1.8.

[0043] In some embodiments, 1%≤W≤5.4%. In some embodiments, W is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.4% or any value therebetween. In some embodiments, 2%≤W≤5%.

[0044] In some embodiments, 10%≤Z≤40%. In some embodiments, Z is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value therebetween. In some embodiments, 20%≤Z≤30%.

[0045] In some embodiments, 0.2≤B≤3. In some embodiments, B is 0.2, 0.5, 1, 1.5, 2, 2.5, 3, or any value therebetween. In some embodiments, 0.6≤B≤2.

[0046] In some embodiments, the mass percentage of the acrylic acid-acrylonitrile copolymer binder is 1% to 15% based on the mass of the negative electrode active material layer. In some embodiments, the mass percentage of the acrylic acid-acrylonitrile copolymer binder is 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 15% or any value therebetween based on the mass of the negative electrode active material layer. In some embodiments, the mass percentage of the acrylic acid-acrylonitrile copolymer binder is 2% to 5% based on the mass of the negative electrode active material layer.

[0047] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite. In some embodiments, the graphite includes artificial graphite or natural graphite. In some embodiments, the mass percentage of the graphite is 70% to 97% based on the mass of the negative electrode active material layer. In some embodiments, the mass percentage of the graphite is 70%, 75%, 80%, 85%, 90%, 97% or any value therebetween based on the mass of the negative electrode active material layer.

[0048] In some embodiments, the negative electrode active material layer further includes a first binder, the first binder including at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, epoxy resin and nylon; based on the mass of the negative electrode active material layer, the mass percentage of the first binder is 1% to 10%. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the first binder is 1%, 2%, 4%, 6%, 8%, 10% or any value therebetween.

[0049] In some embodiments, the negative electrode active material layer further includes a conductive agent, the conductive agent includes: at least one of carbon black, acetylene black, carbon nanotubes, carbon fibers, Ketjen black, artificial graphite, natural graphite and graphene; based on the mass of the negative electrode active material layer, the mass percentage of the conductive agent is 0.8% to 5%. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the conductive agent is 0.8%, 1%, 2%, 3%, 4%, 5% or any value therebetween.

[0050] In some embodiments, the negative electrode active material layer further includes a silicon-based material, and the silicon-based material includes at least one of silicon, silicon alloy, silicon oxygen and silicon carbon; based on the mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 3% to 20%. In some embodiments, the negative electrode active material layer includes silicon oxygen and / or silicon carbon, and the silicon oxygen can be ordinary silicon oxygen (SiOx, 0.5≤x≤1.5), carbon-coated silicon oxygen (SiOx / C) or carbon-coated pre-lithium silicon oxygen (SiOx-Li / C), and the silicon carbon can be ground silicon carbon or deposited silicon carbon. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 3%, 5%, 8%, 10%, 12%, 14%, 15%, 18%, 20% or any value therebetween.

[0051] In some embodiments, the negative electrode plate further includes a current collector, the negative electrode active material layer is disposed on the surface of the current collector, and the resistivity of the negative electrode plate is 0.1Ω·cm to 0.15Ω·cm. In some embodiments, the resistivity of the negative electrode plate is 0.1Ω·cm, 0.11Ω·cm, 0.12Ω·cm, 0.13Ω·cm, 0.14Ω·cm, 0.15Ω·cm or any value therebetween. As a result, the resistivity of the negative electrode plate decreases, which can further improve the rate and cycle performance of the battery. In some embodiments, the current collector of the negative electrode plate includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0052] In summary, the negative electrode sheet provided by the present application effectively improves the lithium ion migration rate, increases the kinetic performance, reduces the DCR, and increases the adhesion between the binder and the current collector, and the adhesion between the binder and the graphite particles. The binder has enhanced toughness and thus alleviates the stress caused by the expansion of the negative electrode active material, and overall prolongs the calendar life of the secondary battery using the negative electrode sheet. Therefore, based on the above improvements, the secondary battery of the present application has at least one of the following advantages: excellent first coulomb efficiency and calendar life.

[0053] 2. Secondary battery

[0054] The present application also provides a secondary battery, the secondary battery comprising the above-mentioned negative electrode plate. Thus, the secondary battery can have all the features and advantages of the negative electrode plate described above, which will not be described in detail here.

[0055] In some embodiments, the secondary battery further includes a positive electrode sheet, an electrolyte, and a separator.

[0056] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0057] In some embodiments, the positive electrode active material comprises a lithium nickel transition metal oxide; wherein the lithium nickel transition metal oxide comprises LiNi m A 1-m O2, A includes at least one of cobalt, manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, yttrium, lanthanum, silver and niobium, 0.1≤m≤1.

[0058] In some embodiments, m is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any value therebetween.

[0059] In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, and Ni95.

[0060] In some embodiments, the positive electrode active material layer further includes a binder and a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc. In some embodiments, the conductive material includes: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0061] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be obtained by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.

[0062] In some embodiments, the electrolyte includes a lithium salt, a solvent, and an additive.

[0063] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), trifluorosulfonyl lithium (LiTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium bis(fluoromalonate)borate (LiBFMB), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiDFP), lithium difluorobis(oxalatophosphate), and lithium 4,5-dicyano-2-(trifluoromethyl)imidazole (LiTDI).

[0064] In some embodiments, the mass percentage content of the lithium salt is 4% to 25% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage content of the lithium salt is 6% to 18%.

[0065] In some embodiments, the solvent includes at least one of a linear carbonate, a cyclic carbonate, and a carboxylic acid ester.

[0066] In some embodiments, linear carbonate is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate and fluorinated linear carbonate. In some embodiments, cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate and butylene carbonate. In some embodiments, carboxylic acid ester includes at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, gamma-butyrolactone and fluorinated carboxylic acid ester.

[0067] In some embodiments, the mass percentage content of the solvent is 40% to 80% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage content of the solvent is 50% to 70%.

[0068] In some embodiments, the additive includes at least one of a cyclic carbonate containing a carbon-carbon double bond, a phosphate containing a silane group, and a nitrile compound.

[0069] In some embodiments, the additive includes at least one of vinylene carbonate (VC), vinyl ethylene carbonate, tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), succinonitrile, adiponitrile, glutaronitrile and hexanetrinitrile. In some embodiments, the additive also includes at least one of methylene methyl disulfonate (MMDS), ethylene ethyl disulfonate, 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), vinyl sulfate (DTD), 4-methyl ethylene sulfate (PCS), 4-ethyl ethylene sulfate (PES), 4-propyl ethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES).

[0070] In some embodiments, the mass percentage content of the additive is 0.05% to 10% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage content of the additive is 0.1% to 5%.

[0071] In some embodiments, a separator is provided between the positive electrode plate and the negative electrode plate to prevent short circuit. The material and shape of the separator that can be used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0072] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene / polyethylene / polypropylene three-layer film can be selected.

[0073] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0074] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0075] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).

[0076] In some embodiments, the method for preparing the secondary battery includes providing an electrode assembly, injecting liquid, packaging and forming. In some embodiments, the temperature of the forming is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C.

[0077] In some embodiments, the formation includes: charging to 3.9V at 0.05C current and standing for 24h at a temperature of 40°C to 50°C, such as 45°C, and a pressure of 150kgf to 750kgf, such as 600kgf, followed by charging to 4.4V at 0.1C, and then discharging to 2.8V at 0.2C.

[0078] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0079] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0080] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.

[0081] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0082] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0083] 3. Device

[0084] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module and battery pack. Therefore, the device can have all the features and advantages of the above-mentioned secondary battery, battery module or battery pack, which will not be repeated here.

[0085] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.

[0086] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0087] Examples and Comparative Examples

[0088] Example 1

[0089] The preparation steps of the acrylic acid-acrylonitrile copolymer binder are as follows: acrylic acid monomer, acrylic acid ester monomer (specifically methyl acrylate monomer), acrylonitrile monomer and water are added into a reaction container at a molar ratio of 1:1:1, heated to a reaction temperature under a protective atmosphere, and then an initiator is added to initiate a reaction. After the reaction is completed for 3 to 6 hours, a first product is obtained after filtering, drying, crushing and sieving, and then a LiOH aqueous solution is added to replace the position of H in -COOH. The acrylic acid-acrylonitrile copolymer binder (PAA-Li-PAN) solution to be finally obtained is determined by adjusting the amount of LiOH added and monitoring the pH value, so that the final mass percentage of the Li element is 2.8%.

[0090] The preparation steps of the negative electrode are as follows: select a specific surface area of ​​0.82m 2 / g of graphite as the main material, the negative electrode active material graphite, acrylic acid-acrylonitrile copolymer binder, conductive agent carbon black (Super-P), second binder CMC, SBR and PAA are mixed in a mass ratio of 82:14:1:0.6:1.2:1.2, deionized water is added, and the mixture is stirred under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on an 8μm negative electrode current collector copper foil, and the single-side coating weight is 8mg / cm 2 , and then the negative electrode sheet is obtained through drying, rolling, hot pressing and other steps.

[0091] The preparation steps of the positive electrode plate are as follows: the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, CNT (conductive agent carbon nanotube) / Super-P, binder polyvinylidene fluoride PVDF, the positive electrode active materials are in the weight ratio: CNT / Super-P:PVDF=95:(1.0 / 2.0):2 in N-methylpyrrolidone NMP, and after sufficient homogenization, they are coated on a 12μm thick aluminum current collector, and then the positive electrode sheet is obtained through drying, rolling, hot pressing and other steps.

[0092] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), fully dissolve the lithium salt LiPF6 in a mixed solution of EC / DEC / EMC (ethylene carbonate / diethyl carbonate / ethyl methyl carbonate) = 25 / 20 / 55 to prepare a 1 mol / L solution.

[0093] Diaphragm: PP / PE / PP (polypropylene / polyethylene / polypropylene) three-layer composite diaphragm is used.

[0094] Preparation of lithium-ion secondary batteries: The positive electrode sheets, separators, and negative electrode sheets prepared above are overlapped in sequence, with the separator being located between the positive electrode sheets and the negative electrode sheets, and are wound to obtain bare cells. After being fully dried, the bare cells are placed in a cylindrical (e.g., 18650 cylindrical) steel shell, and then the electrolyte prepared above is injected and sealed. After the battery is pre-charged, high-temperature infiltrated, formed (the formation conditions are: temperature 45°C, 0.05C current charged to 3V and then allowed to stand for 5 minutes, then 0.1C charged to 3.5V and then allowed to stand for 5 minutes, and then 0.33C charged to 4.0V) and high-temperature aged, it is subjected to constant capacity division.

[0095] Examples 2 to 5 and Comparative Examples 1 to 2

[0096] Examples 2 to 5 and Comparative Examples 1 to 2 are achieved on the basis of Example 1 by adjusting the mass percentage content of alkali metal elements, the mass percentage content of acrylonitrile units, and the specific surface area of ​​graphite in the acrylic acid-acrylonitrile copolymer binder. Specific adjustment measures and detailed data are shown in Table 1.

[0097] Test Method

[0098] 1. Specific surface area test

[0099] The specific surface area can be measured by a fully automatic pore volume and pore size specific surface area analyzer. Before testing, the sample needs to be thoroughly dried and degassed at 90°C for 10 hours to remove the gas / moisture adsorbed on the sample surface. During the test, the sample is first weighed and placed in liquid nitrogen to plot the nitrogen adsorption-desorption curve at 77K. The specific surface area S of the sample is then calculated by the Brunauer-Emmett-Teller (BET) method. For example, the specific surface area of ​​graphite can be tested.

[0100] 2. Inductively coupled plasma emission spectrometer (ICP) test

[0101] The mass percentage content of alkali metal elements (such as Li) in acrylic acid-acrylonitrile copolymer binder can be quantitatively analyzed by ICP. Specifically: weigh about 0.05g (accurate to 0.00001g) of the sample in a 50mL beaker, add 8.0mL of 1+1 hydrochloric acid, place it on an electric furnace and heat it at low temperature to dissolve, add 5 drops of hydrogen peroxide and a small amount of water after the sample is basically dissolved, heat it until the solution does not emit small bubbles, then remove and cool it. Transfer and make up the volume in a 100mL volumetric flask, and do a blank experiment at the same time. The content of alkali metal elements in acrylic acid-acrylonitrile copolymer binder can be obtained by the above-mentioned test method.

[0102] 3. Impedance (DCR) test

[0103] Before the cycle capacity retention rate test, the lithium-ion battery was discharged to 2.5V at 1C constant current at 25±2℃, then charged to 4.25V at 0.5C constant current, and charged to 0.05C at 4.25V, and then discharged to 50% SOC at 1C constant current, and left to stand for 60 minutes, and the voltage U1 after the end of the standing was recorded, and then discharged at 2C constant current for 10s, and the voltage U2 after the discharge was recorded, and the 2C current was recorded as I, and left to stand for 60 minutes. According to the formula DCR = (U1-U2) / I, the discharge DCR (impedance) of the battery at 50% SOC is calculated.

[0104] 4. 25℃ Cyclic Capacity Retention Test

[0105] At 25°C, the prepared lithium-ion secondary battery was charged to 4.25V at a constant current rate of 0.5C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 30 minutes, it was discharged to 2.5V at a rate of 1C, and stood for 30 minutes, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 300 times by the above method, and the discharge capacity was recorded each time. The capacity retention rate of the lithium-ion secondary battery after 300 cycles at 25°C = the discharge capacity of the 300th time / initial discharge capacity × 100%.

[0106] 5. High temperature storage performance test

[0107] At 25°C, the prepared lithium-ion secondary battery was charged to 4.25V at a constant current rate of 0.5C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 0.5C, and the initial discharge capacity C0 was recorded. At 25°C, the prepared lithium-ion secondary battery was charged to 4.25V at a constant current rate of 0.5C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was placed in a 45°C oven for storage for 28 days. After the storage is completed, it is taken out and cooled to a constant temperature of 25°C, and discharged to 2.5V at a rate of 0.5C, and the discharge capacity is recorded, which is the capacity retention C1. Then it is charged to 4.25V at a constant current rate of 0.5C, and then charged at a constant voltage until the current is less than 0.05C. After standing for 5 minutes, discharge the battery to 2.5V at a rate of 0.5C, and record the discharge capacity after high-temperature storage. Repeat this charge and discharge cycle 3 times, and take the third discharge capacity as C2.

[0108] The capacity retention rate of the lithium ion secondary battery after storage at 45° C. for 28 days=C1 / C0×100%.

[0109] The capacity recovery rate of the lithium ion secondary battery after storage at 45°C for 28 days = C2 / C0×100%.

[0110] Test Results

[0111] Table 1

[0112]

[0113] It can be seen from Examples 1 to 5 and Comparative Examples 1 to 2 that the negative electrode plate provided by the present application uses acrylic acid-acrylonitrile copolymer as the negative electrode binder, and by controlling the content of alkali metal elements, the content of acrylonitrile units, and the specific surface area of ​​graphite in the acrylic acid-acrylonitrile copolymer binder, on the one hand, the lithium ion migration rate is effectively improved, the kinetic performance is increased, the DCR is reduced, and the first efficiency is improved; on the other hand, through the above-mentioned control, the stability of the binder and the plate hardness are improved, the adhesion between the binder and the current collector, and the adhesion between the binder and the negative electrode graphite particles are simultaneously improved, the toughness of the binder is enhanced, and the stress caused by the expansion of the negative electrode silicon-based material is alleviated, thereby extending the calendar life of the secondary battery using the negative electrode plate as a whole.

[0114] By comparing Comparative Example 1 with Examples 1 to 5, it can be seen that due to the excessively large specific surface area of ​​graphite, the excessively large mass percentage of Li element in PAA-Li-PAN, and the excessively small mass percentage of PAN in PAA-Li-PAN, the value of (1-Z)*B+W is too large, thereby increasing the DCR of the secondary battery, and deteriorating the cycle performance and high-temperature storage performance.

[0115] By comparing Comparative Example 2 with Examples 1 to 5, it can be seen that due to the small specific surface area of ​​graphite, the small mass percentage of Li element in PAA-Li-PAN, and the large mass percentage of PAN in PAA-Li-PAN, the value of (1-Z)*B+W is too small. As a result, the lithium ion transport performance of PAA-Li-PAN is poor, and it has little contact with the surface of large-sized graphite particles and weak adhesion, which leads to an increase in the DCR of the secondary battery, and deterioration of the cycle performance and high-temperature storage performance.

[0116] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.

Claims

1. A negative electrode plate, characterized in that: The invention comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises graphite and an acrylic acid-acrylonitrile copolymer binder, wherein the acrylic acid-acrylonitrile copolymer binder comprises: a first acrylic acid unit, a second acrylic acid unit and an acrylonitrile unit, wherein at least one of the first acrylic acid unit and the second acrylic acid unit contains an alkali metal element, wherein the alkali metal element comprises at least one of Li, Na and K; The negative electrode plate satisfies: 0.2≤(1-Z)×B+W≤3; Wherein, based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the alkali metal element is W, and the mass percentage content of the acrylonitrile unit is Z; The specific surface area of ​​the graphite is B, in m 2 / g.

2. The negative electrode sheet according to claim 1, characterized in that: The chemical structural formula of the acrylic acid-acrylonitrile copolymer binder is shown in Formula I: Wherein, a is an integer greater than 0, b is an integer greater than or equal to 0, and c is an integer greater than 0; R1 includes at least one of H, Li, Na and K, and at least one R1 is at least one of Li, Na and K; R2 includes at least one of substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C3-C6 cycloalkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C6-C12 aryl and substituted or unsubstituted C6-C12 heteroaryl, wherein the substituent includes at least one of halogen, alkyl, aryl or heteroaryl.

3. The negative electrode sheet according to claim 2, characterized in that: b is an integer greater than 0; and / or R1 includes at least one of H and Li, and at least one R1 is Li; R2 includes at least one of C1-C3 alkyl, C3-C6 cycloalkyl, C2-C3 alkenyl, C2-C3 alkynyl, C6-C12 aryl and C6-C12 heteroaryl; and / or The average molecular weight of the acrylic acid-acrylonitrile copolymer binder is 700,000 to 900,000; and / or Based on the mass of the acrylic acid-acrylonitrile copolymer binder, the mass percentage content of the first acrylic acid unit is 60% to 90%, and the mass percentage content of the second acrylic acid unit is 0% to 30%.

4. The negative electrode sheet according to claim 1, characterized in that: The acrylic acid-acrylonitrile copolymer binder includes a copolymer formed by copolymerization of a first acrylic acid monomer, a second acrylic acid monomer and an acrylonitrile monomer and partial substitution with an alkali metal; wherein the molar ratio of the first acrylic acid monomer, the second acrylic acid monomer and the acrylonitrile monomer is 1:(0.5-1.5):(0.5-1.5); the chemical structural formula of the first acrylic acid monomer is shown in Formula II, the chemical structural formula of the second acrylic acid monomer is shown in Formula II, and the chemical structural formula of the acrylonitrile monomer is shown in Formula IV: Wherein, R2 includes substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C3-C6 cycloalkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C6-C12 heteroaryl, wherein the substituent includes at least one of halogen, alkyl, aryl or heteroaryl.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: 0.5≤(1-Z)×B+W≤1.5; and / or 1% ≤ W ≤ 5.4%; and / or 10% ≤ Z ≤ 40%; and / or 0.2≤B≤3。 6. The negative electrode sheet according to claim 5, characterized in that: 2% ≤ W ≤ 5%; and / or 20% ≤ Z ≤ 30%; and / or 0.6≤B≤2。 7. The negative electrode sheet according to claim 1, characterized in that: Based on the mass of the negative electrode active material layer, the mass percentage of the acrylic acid-acrylonitrile copolymer binder is 1% to 15%; and / or The graphite includes at least one of artificial graphite and natural graphite; based on the mass of the negative electrode active material layer, the mass percentage of the graphite is 70% to 97%; and / or The negative electrode active material layer further includes a first binder, the first binder including at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, epoxy resin and nylon; based on the mass of the negative electrode active material layer, the mass percentage of the first binder is 1% to 10%; and / or The negative electrode active material layer further includes a conductive agent, wherein the conductive agent includes at least one of carbon black, acetylene black, carbon nanotubes, carbon fibers, Ketjen black, artificial graphite, natural graphite and graphene; based on the mass of the negative electrode active material layer, the mass percentage of the conductive agent is 0.8% to 5%; and / or The negative electrode active material layer further includes a silicon-based material, which includes at least one of silicon, silicon alloy, silicon oxygen and silicon carbon; based on the mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 3% to 20%.

8. The negative electrode sheet according to claim 1, characterized in that: The negative electrode plate further includes a current collector, the negative electrode active material layer is arranged on the surface of the current collector, and the resistivity of the negative electrode plate is 0.1 Ω·cm to 0.15 Ω·cm.

9. A secondary battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 1 to 8.

10. A device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Cited By

  • Graphite material, negative electrode sheet, battery, and electrical device

    WO2026194755A1